# Which if the following is the simplified form of 2^(1-n)*(sqrt 8)^n/ (sqrt 2)^(-n).Options: 1. 2^n 2. 2^(-n) 3. 2^(n-1) 4. 2^(n+1)

### 2 Answers | Add Yours

The following expression has to be simplified: 2^(1 - n)*(sqrt 8)^n)/(sqrt 2)^-n

2^(1 - n)*(sqrt 8)^n)/(sqrt 2)^-n

=> 2^(1 - n)*(2^(3/2)^n)/(2^(-n/2))

=> 2^(1 - n)*(2^(3n/2)/(2^(-n/2))

=> 2^(1 - n)*(2^(3n/2 + n/2)

=> 2^(1 - n)*(2^(2n))

=> 2^1*2^(2n - n)

=> 2^1*2^n

=> 2^(1+n)

**The required result is option 4: 2^(n+1)**

First of all, we'll write sqrt8 as a power of 2:

sqrt8 = (8)^(n/2) = (2^3)^(n/2) = 2^(3n/2)

Now, we'll multiply 2^(3n/2) by 2^(1-n).

Since the bases are matching, we'll add the exponents:

2^(3n/2) *2^(1-n) = 2^(3n/2 + 1 - n) = 2^(n/2 + 1)

Now, we'll write the denominator as a power of 2:

(sqrt2)^(-n) = 2^(-n/2)

Now, we'll re-write the ratio:

2^(n/2 + 1)/2^(-n/2) = 2^(n/2 + 1+ n/2)

2^(n/2 + 1+ n/2) = 2^(2n/2 + 1)

2^(2n/2 + 1) = 2^(n+1)

**The correct option is the 4th: 2^(n+1).**